Implementasi Kurikulum Tingkat Satuan Pendidikan dalam Pelajaran Bahasa Di Kelas V Sekolah Dasar - Dyaristya E. P. Wismasari; Agus Wedi; Eka Pramono Adi (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2016)
This study aims to describe the planning, process implementation, and assessment of learning outcomes in language lessons in grade V elementary school. This study used a descriptive research design with observation, documentation, and interview methods. The results showed that the learning process planning had been carried out by each language teacher; the implementation of the learning process is carried out in accordance with the lesson plan, and the assessment of learning outcomes is carried out through daily tests and semester tests.